Agricultural growth and rural performance a Philippine perspective - Balisacan, Arsenio M.
This paper shows that rural poverty in the Philippines was substantially unaffected by the rapid agricultural growth during the Green Revolution period. Both demand and supply consideration constrained the responses of the rural sector to the stimulus provided by rapid agricultural growth.
Keywords: Rural poor -- Philippines; Agriculture -- Philippines; Rural development -- Philippines